2019
DOI: 10.1002/ece3.5566
|View full text |Cite
|
Sign up to set email alerts
|

Variation in sex allocation plasticity in three closely related flatworm species

Abstract: Sex allocation (SA) theory for simultaneous hermaphrodites predicts an influence of group size on SA. Since group size can vary within an individual's lifetime, this can favor the evolution of phenotypically plastic SA. In an emerging comparative context, we here report on SA plasticity in three closely related Macrostomum flatworm species, namely Macrostomum janickei, Macrostomum cliftonensis, and Macrostomum mirumnovem. For each species, we experimentally raised worms in three group sizes (isolated, pairs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…And by confirming that all maternal offspring of the GFP-negative M. janickei were GFP-positive, we could ascertain that the GFP-positive BAS1 M. lignano had indeed sired these F1 hybrids. Moreover, previous experiments had shown that neither species self-fertilizes over a comparable observation period 60 , 61 , thus any offspring produced in the heterospecific pairs must have resulted from outcrossing with the partners.…”
Section: Methodsmentioning
confidence: 99%
“…And by confirming that all maternal offspring of the GFP-negative M. janickei were GFP-positive, we could ascertain that the GFP-positive BAS1 M. lignano had indeed sired these F1 hybrids. Moreover, previous experiments had shown that neither species self-fertilizes over a comparable observation period 60 , 61 , thus any offspring produced in the heterospecific pairs must have resulted from outcrossing with the partners.…”
Section: Methodsmentioning
confidence: 99%
“…The journal's Online ISSN is 1439‐0469 and it is archived in CLOCKSS. Note that these names have also appeared in the electronic 'Early View' edition of another article from our group (Singh, Vellnow, & Schärer, ), but since that work was not intended to conform to the ICZN requirements, having an experimental rather than taxonomic focus, these names cannot be considered available from that work.…”
Section: Methodsmentioning
confidence: 99%
“…22, with the SA data reported in, respectively, Giannakara and Ramm (2017), Winkler and Ramm (2018), and Supplementary Information S1. An additional four species are reciprocally mating, namely M. janickei Schärer, 2019, M. cliftonense Schärer and Brand, 2019, and M. mirumnovem Schärer and Brand, 2019(Schärer et al 2020Zhang et al 2021), with the SA data reported in Singh et al (2020b), plus multiple studies in M. lignano Ladurner, Schärer, Salvenmoser, andRieger, 2005 (Ladurner et al 2005), with the SA data reported in several studies (see below). Details of all the SA studies are given in Supplementary Table S1.…”
Section: Study Speciesmentioning
confidence: 99%
“…The species M. mirumnovem (Singh et al 2020b) and all three hypodermically inseminating species (Ramm et al 2012(Ramm et al , 2015Giannakara and Ramm 2017, this study) can self-fertilize, and were classified accordingly. Moreover, we classified species as either reciprocally mating or hypodermically inseminating using both behavioural and morphological data.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation